The influence of ulū al-albāb in social accounting for community-interest corporations - Mhd. Sarif, Suhaimi; Ismail, Yusof (2015)
This study aims to explore the influence of Ulū al-albāb in practising social accounting for community-interest corporations. Ulū al-albāb is distinctive term used in Islam to refer to individuals who are endowed with clear understanding about life and life is connected to the Hereafter world. The basis for Ulū al-albāb is based on Tawhidic paradigm, a value that unifies the differences and diversity for the sake betterment for oneself and the community in this world and beyond. Accounting is about informing financial performance through a standard of book keeping, recording, and interpreting performance of corporations. Social accounting prepares and makes the reports financial standing with key stakeholders. This study argues that accounting personnel with ulū al-albāb characteristics enhances their roles to practice sustainability social accounting for the performance of community-interest corporations to service beyond financial performance. The study uses personal interview with accounting personnel at community-interest corporations in Malaysia to solicit their views on the level of ulū al-albāb influence in the social accounting for their community interest corporations (CIC). The preliminary results suggest that the concern about social well-being motivates community interest corporations to employ accounting personnel with accounting for public sector of non-profit corporations to bring the CIC to the social responsibility and accountability to the stakeholders and beyond. The results of the study are based on personal interview that could not be easily generalized. Policy makers on community interest corporations will apply ulū al-albāb in the training of accounting personnel with ulū al-albāb characteristics.